The Effectiveness of Preventative Mass Vaccination Regimes Against the Incidence of Highly Pathogenic Avian Influenza on Java Island, Indonesia. Issue 2 (23rd May 2013) - Bett, B.; McLaws, M.; Jost, C.; Schoonman, L.; Unger, F.; Poole, J.; Lapar, M. L.; Siregar, E. S.; Azhar, M.; Hidayat, M. M.; Dunkle, S. E.; Mariner, J.
Summary We conducted an operational research study involving backyard and semicommercial farms on Java Island, Indonesia, between April 2008 and September 2009 to evaluate the effectiveness of two preventive mass vaccination strategies against highly pathogenic avian influenza (HPAI). One regimen used Legok 2003 H5N1 vaccine, while the other used both Legok 2003 H5N1 and HB1 Newcastle disease (ND) vaccine. A total of 16 districts were involved in the study. The sample size was estimated using a formal power calculation technique that assumed a detectable effect of treatment as a 50% reduction in the baseline number of HPAI‐compatible outbreaks. Within each district, candidate treatment blocks with village poultry populations ranging from 80 000 to 120 000 were created along subdistrict boundary lines. Subsequently, four of these blocks were randomly selected and assigned one treatment from a list that comprised control, vaccination against HPAI, vaccination against HPAI + ND. Four rounds of vaccination were administered at quarterly intervals beginning in July 2008. A vaccination campaign involved vaccinating 100 000 birds in a treatment block, followed by another 100 000 vaccinations 3 weeks later as a booster dose. Data on disease incidence and vaccination coverage were also collected at quarterly intervals using participatory epidemiological techniques. Compared with the unvaccinated (control) group, the incidence of HPAI‐compatible events declined by 32% (P = 0.24) in the HPAI‐vaccinated group and by 73% (P = 0.00) in the HPAI‐ and ND‐vaccinated group. The effect of treatment did not vary with time or district. Similarly, an analysis of secondary data from the participatory disease and response (PDSR) database revealed that the incidence of HPAI declined by 12% in the HPAI‐vaccinated group and by 24% in the HPAI + ND‐vaccinated group. The results suggest that the HPAI + ND vaccination significantly reduced the incidence of HPAI‐compatible events in mixed populations of semicommercial and backyard poultry.